Protective Role of Whey Protein Isolate on MPP+-Induced Differentiation of SH-SY5Y Cells by Modulating the Nrf2 Antioxidant Pathway - Panlekha Rungruang; Morakot Sroyraya; Veerawat Sansri (Molecules)
The pathogenesis of Parkinson’s disease (PD) consists of the apoptosis of dopaminergic neurons in the substantia nigra pars compacta (SNpc) due to oxidative stress. The present study aimed to evaluate the potential antioxidant activity of whey protein isolate (WPI) in PD models, using neurotoxin-exposed SH-SY5Y cells differentiated into dopaminergic-like neurons. Our research shows that WPI’s high glutamic acid, aspartic acid, and leucine contribute to its antioxidant and neuroprotective effects, with glutamic acid crucial for glutathione synthesis. In vitro studies found that WPI, at concentrations of 5–1000 µg/mL, is non-toxic to differentiated SH-SY5Y cells. Notably, the lowest con-centration of WPI (5 µg/mL) significantly decreased intracellular reactive oxygen species (ROS) levels in these cells following a 24 h co-treatment with 1-methyl-4-phenylpyridinium (MPP+). The antioxidant effects of WPI were also confirmed by the increased expression of HO1 and GPx antioxidant enzymes, which are Nrf2 pathway target genes and were evaluated by real-time PCR. Furthermore, Nrf2 nuclear translocation in the differentiated SH-SY5Y cells was also increased when the cells were exposed to 5 µg/mL of WPI with MPP+. These results together suggest that WPI has antioxidant effects on dopaminergic-like neurons in a Parkinson’s disease model.